Legal Philosophy Values in the Law Formation in Indonesia - Agustina, Ria; Anas, Kamal; Jalaluddin, Jalaluddin; Fikri, Ahmad Ma’mun (IHSA Institute, 2025)
The most significant influence on the development of Indonesian law is legal philosophy. The term